Preoperative autologous blood donation and transfusion in dogs undergoing elective surgical oncology procedures with high risk of hemorrhage. Issue 3 (26th February 2021) - Sharma, Surabhi; Boston, Sarah E.; Kotlowski, Jerzy; Boylan, Matthew
Abstract: Objective: To describe preoperative autologous blood donation (PABD) and transfusion in dogs undergoing elective surgical oncology procedures with a high risk of intraoperative hemorrhage. Study design: Prospective study. Animals: Twelve dogs. Methods: Dogs undergoing surgical oncology procedures associated with a high risk of hemorrhage were enrolled. Blood was collected a minimum of 6 days before surgery and separated into fresh frozen plasma (FFP) and packed red blood cells (pRBC). Dogs received FFP at the start of surgery and pRBC intraoperatively when hemorrhage ensued. The mean packed cell volume/total solids (PCV/TS) were calculated on the day of PABD preoperatively, immediately postoperatively, and 24 hours after transfusion. The dogs were monitored for transfusion‐related adverse reactions, including hyperthermia, hypotension, tachycardia, bradycardia, pale mucous membranes, prolonged capillary refill time, or tachypnea/dyspnea. Results: Dogs enrolled in the study underwent mandibulectomy, maxillectomy, chest wall resection, and liver lobectomy. Ten of the 12 dogs that underwent PABD received autologous transfusion at first signs of hemorrhage intraoperatively. Iatrogenic anemia was noted in two dogs (PCV 30% and 31%). The mean PCV/TS levels on the day of blood collection, preoperatively, immediately postoperatively (after transfusion), and 24 hours posttransfusion were 45.1%/7.1 g/dL, 42.2%/6.73 g/dL, 33.2%/5.42 g/dL, and 36.5%/5.65 g/dL, respectively. No dog developed transfusion‐related complications. Conclusion: Preoperative autologous blood donation was well tolerated and led to uneventful autologous transfusion in 10 of 12 dogs. Clinical significance: Preoperative autologous blood donation and autologous transfusion are feasible for dogs undergoing elective surgical procedures with a high risk of hemorrhage.